Determinants and Characteristics of Angle-Closure Disease in an Elderly Chinese Population. (April 2015) - Ko, Yu-Chieh; Liu, Catherine J.; Hsu, Wen-Ming; Cheng, Ching-Yu; Kuang, Tung-Mei; Chou, Pesus
ABSTRACT Purpose: To determine factors associated with angle-closure disease, particularly in those with structural or functional damage to the eyes, in an elderly Chinese population. Methods: A total of 460 individuals aged over 72 years were recruited. The association of angle-closure diseases, including primary angle-closure suspect (PACS), primary angle-closure (PAC) and primary angle-closure glaucoma (PACG), with various systemic and ocular characteristics was evaluated using multivariate logistic regression analyses. Results: Of 374 phakic subjects, 199 (53.2%) had angle-closure disease, including 135 PACS, 46 PAC, and 18 PACG. The majority of those with untreated PACG (10/13, 76.9%) had presenting intraocular pressure (IOP) < 20 mmHg. Independent risk factors for angle-closure disease were lower Van Herick grading, shallower central anterior chamber depth (ACD), and higher post-mydriatic IOP (all p < 0.05). Central and peripheral ACD estimation correlated weakly, only 60.8% of angle-closure eyes had generalized narrowing of ACD as a Van Herick grading ≤2 and central ACD ≤ 2.83 mm. A criterion considering either central or peripheral ACD identified 91% of angle-closure eyes, including all PACG. A higher post-mydriatic IOP was associated with a diagnosis of PAC or PACG among angle-closure eyes (p = 0.002). Conclusion: Both central and peripheral ACD should be evaluated and shallowing of either one should be an indication for gonioscopic examination to maximize detection of angle-closure disease in elderly Chinese persons. PAC and PACG were associated with higher post-mydriatic IOP than PACS, although subjects with PACG frequently presented with normal IOP.